2020
DOI: 10.1002/eji.201948451
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated RASGRP1 expression through RUNX1 mediated transcription promotes autoimmunity

Abstract: RasGRP1 is a Ras guanine nucleotide exchange factor, and an essential regulator of lymphocyte receptor signaling. In mice, Rasgrp1 deletion results in defective T lymphocyte development. RASGRP1‐deficient patients suffer from immune deficiency, and the RASGRP1 gene has been linked to autoimmunity. However, how RasGRP1 levels are regulated, and if RasGRP1 dosage alterations contribute to autoimmunity remains unknown. We demonstrate that diminished Rasgrp1 expression caused defective T lymphocyte selection in C5… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…It is believed that aberrant expression of RASGRP1 plays an important part in the development of autoimmunity. According to Baars et al [ 33 ], dysregulation of RASGRP1 often takes place in activated T cells and may, in a dose-dependent way, affect TCR-induced signaling as well as thymocyte selection. The immune response hypothesis of IC/BPS etiology [ 27 ], which is partly explained by this finding, suggests that RASGRP1 may have potential significance to the immunological environment of IC/BPS.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that aberrant expression of RASGRP1 plays an important part in the development of autoimmunity. According to Baars et al [ 33 ], dysregulation of RASGRP1 often takes place in activated T cells and may, in a dose-dependent way, affect TCR-induced signaling as well as thymocyte selection. The immune response hypothesis of IC/BPS etiology [ 27 ], which is partly explained by this finding, suggests that RASGRP1 may have potential significance to the immunological environment of IC/BPS.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it was shown that suppressing RasGRP1 inhibited neuroinflammation [ 25 ]. Additionally, Baars et al showed that decreased RasGRP1 reduced active inflammatory disease [ 26 ]. However, the impact of RasGRP1 on sepsis-induced AKI is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, humans deficient in RasGRP1 have increased numbers of TCRγδ+ CD8+ T cells [ 58 ]. RasGRP1-deficient mice develop splenomegaly and autoantibodies as a result of T cell dysregulation, characterized by an elevated interleukin (IL)-4 secretion [ 31 , 59 , 60 , 61 ]. This elevation in IL-4 drives B cell proliferation and the production of autoantibodies [ 60 ].…”
Section: Rasgrp1: Cell Development and Functionmentioning
confidence: 99%
“…This elevation in IL-4 drives B cell proliferation and the production of autoantibodies [ 60 ]. Furthermore, one study found that the binding of RUNX1 to a putative autoimmunity-associated enhancer 1 upstream of Rasgrp1 mediates the RasGRP1 deficiency-mediated autoimmune disease [ 61 ].…”
Section: Rasgrp1: Cell Development and Functionmentioning
confidence: 99%